Water-soluble adhesive for stable long-term ambulatory EEG recordings. (October 2022) - Nurse, Ewan S.; Marlow, Kristan; Hennessy, Patrick J.; Knight-Sadler, Rory; Nelson, Tim; Freestone, Dean R.; Slater, Kyle D.; Cook, Mark J.
Highlights: A novel water-soluble adhesive provides high integrity EEG recordings. They can be used for at-home monitoring for up to 6 days, and can be maintained by patients and carers. Signal integrity was not significantly linked to age or patient regionality of recording, but was linked to electrode position. Abstract: Objective: Conventional methods used to adhere EEG electrodes are often uncomfortable. Here, we present a polymer-based water-soluble EEG adhesive that can be maintained for up to 6 days. The primary outcome measure of this study is the median electrode impedance at day 6. Methods: Impedance measurements for 841 EEG recordings using a 21 channel 10–20 configuration were remotely logged daily for 6 days after connection. A novel electrode adhesive was used to attach EEG electrodes. Patients were instructed to maintain their electrodes on day 4. Results: Median electrode impedances were significantly below 10kOhms for each day of recording, with a median value on day 6 of 4.18kOhms. Impedance values were significantly lower on day 5 than on day 4, demonstrating that the maintenance process can reduce impedance. Except for day 4–5, the median impedance increased each day. No significant difference was found on the first or final day between clinics or residences from areas of different geographic remoteness. Conclusions: EEG is able to be recorded in patients homes for 6 days with acceptable impedance and no significant effect of regionality or patients age. Significance: To the best of our knowledge, this is the first report in the literature of impedance data from long-term ambulatory EEG studies.